A new species of the genus Cottus (Scorpaeniformes, Cottidae) from the Baltic Sea Basin and its phylogenetic placement - Sideleva, Valentina; Kesminas, Vytautas; Zhidkov, Zakhar (European Journal of Taxonomy, 2022)
The genus Cottus contains more than 60 species that are common in freshwater bodies of northern Eurasia and North America. Despite the abundance of species, this genus has been insufficiently studied in Eastern European rivers and lakes. The new taxon Cottus cyclophthalmus sp. nov. was found in the Neman/Nemunas and Venta river systems (Baltic Sea Basin). Cottus cyclophthalmus is sister and most morphologically similar to Cottus gobio. The new species has the following diagnostic characters: round, protruding (tubular) eyes near front of head; dermal papillae on top and sides of head, naked body, absence of bony prickles, full trunk canal with 32–36 pores. The description of Cottus cyclophthalmus and a new finding of Cottus microstomus improved understanding of the Eastern European biodiversity.